Hardness Test on the Alloy Fe-50%atAl With the Addition of Nickel Using Mechanical Alloying Method - Dona Abrini; Sanny Ardhy; Haznam Putra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2017)
Hardness test on the alloy Fe-50% at Al with the addition of nickel were prepared by mechanical alloying method. The powder mixture Fe-50at.%Al with the variation adding 0,5at.%Ni, and 2at.%Ni are grinded using High Energy Milling HEM E-3D in Argon condition for 10 hours. To determine the hardness, conducted to take the sample with the certain time duration to each composition. Then, the sample which has been taken is characterization using hardness. The results showed that the highest hardness properties exist in the alloy Fe-50% at Al-0.5% at Ni, amounting to 161.53 HV. The addition of nickel on alloy reduces the hardness properties of the alloy. However, the addition of nickel require a short time to raise the hardness properties.